Html-Based Digital Flashcard Media to Improve The Mastery of English Vocabulary of 1st Grade - Rahma, Neta Kurnia; Widagdo, Arif (Jurnal Pendidikan Indonesia, 2024)
As the main learning actors, teachers often do not use learning media to support student learning outcomes. This study aims to create a feasible and effective digital flashcard media and determine whether digital flashcard media can improve the mastery of English vocabulary of grade I elementary school students. The press developed digital flashcards. This research uses the RnD method with the ADDIE model. The data collection methods used were questionnaires and tests. In contrast, the data collection instruments used were expert validation sheets collected from the assessment of three experts, as well as responses from a teacher and 20 grade 1 elementary school students and test sheets. The data analysis methods used in this research are qualitative and quantitative data. Qualitative data was obtained from needs analysis data, input and product validation suggestions from media validators, material experts, and linguists, and input and suggestions from teacher and student responses. The results showed a significant increase in students' mastery of English vocabulary, as indicated by the difference in pretest and posttest scores. Thus, it can be concluded that digital flashcard media is considered feasible and effective for student learning to improve their mastery of English vocabulary. This study implies that the use of HTML-based digital learning media can be integrated into the English learning curriculum in elementary schools.